Automated sport facilities booking for Majlis Perbandaran Kajang Sport Arena / Muhammad Razman Husin - Husin, Muhammad Razman (2017)
Majlis Perbandaran Kajang Sport Arena is located in Bandar Baru Bangi, which every day the staff will entertain customers either walk in or call to do their sport facilities booking. Common booking issues like redundancy booking, lost of information and even unpaid booking fee leading to unbooked facility has cause major problem for MPKJ Sport Arena. The Sport Arena does not have any computerized system that could facilitate the facilities booking and there are no computerizing systems to keep their customer information. The target of this work is to develop a facilities booking system for MPKJ Sport Arena. Currently, the customer of MPKJ Sport Arena use the manual method either walk in to Sport Arena or call the operator to know the availability of the facilities. This cause the customer time to booked the facilities. The project was document into five phases which is: Introduction, Literature Review, Methodology, Result and Analysis, and Conclusion and Recommendation. The methodology that has been used in the project is Waterfall Model. The requirements for this project were collected by observation and interview of the stakeholder. It was analyzed using CRUD technique and it was documented in Software Requirement Specification (SRS). The system design and structures were made using eclipse software and it was saved in a Software Development Document (SDD). In the near future, the system should be available and integrated with mobile application system as features of booking facilities can be implemented, since people nowadays tend to use the smartphone more than the web in order handle their matter.